(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Cybersecurity is a major worry for individuals, corporations, and governments as digital technologies grow more prevalent. Cyberattacks are becoming more complex & dynamic, making traditional methods of threat identification and prevention inadequate. In the realm of cybersecurity, AI mostly serves to detect and prevent threats. By utilizing machine learning techniques & extensive data analysis, artificial intelligence may identify patterns and irregularities in network traffic and user behavior that could suggest a possible cyberattack. One way AI can help stop assaults is by using predictive modeling. Also, by looking at previous attacks and finding similarities, AI can anticipate such dangers and take precautions to avoid them. Artificial intelligence plays a crucial role in cybersecurity by enabling the creation of automated incident response systems. In order to minimize interruption and damage, these systems can analyze data, detect possible dangers, and then take action to either limit or lessen the impact of an attack. For cybersecurity purposes, businesses must use AI to safeguard their networks & confidential data from evolving cyber threats. In today’s digital world, AI is quickly becoming an essential tool for effective cybersecurity due to its real-time data analysis capabilities and capacity to automate incident response. AI has several applications in cybersecurity, such as threat detection & prevention, which will be covered in this study.